Association of clinico-epidemiological features with locally advanced stage of cervical cancer patients presenting at Bangabandhu Sheikh Mujib Medical University, Bangladesh: Clinicoepidemiological features of locally advanced cervical cancer (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Cervical cancer is one of the most prevalent gynecological cancers in women in Bangladesh. The objective of this study was to assess the clincoepidemiological association with the histology of locally advanced cervical cancer. We have done this observational study in the department of Clinical Oncology at Bangabandhu Sheikh Mujib Medical University from July to December 2019. Sixty-six biopsy-proven locally advanced (stage IIB to IVA) squamous cell carcinoma of uterine cervix were included in this study. The mean age of patients at diagnosis was 48.5 (±8.6) years. Commonly observed epidemiological characteristics of locally advanced carcinoma cervix were illiteracy (46.9%), oral contraceptive use (62.1%), multi para (78.7%) and early marriage (74.2%). Most frequent clinical presentation was post-coital bleeding (37.87%). Most patients presented in stage IIB (65.1%). The association of the stages of the disease with age, parity, oral contraceptive use, age at marriage and clinical presentation were statistically nonsignificant, whereas illiteracy was statistically significant. Most women had poor awareness regarding their need for routine check-up and screening as indicated by the late medical care seeking. Social stigma might have played some role. Relevant programmes should create awareness among women, especially those with socioeconomic deprivation.BSMMU J 2022; 15(3): 175-179